2021
DOI: 10.1155/2021/6617292
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Binahong (Anredera cordifolia (Tenore) Steenis) Extracts on the Levels of Malondialdehyde (MDA) in Cataract Goat Lenses

Abstract: Cataracts are one of the most causes of blindness in the world. Oxidative stress can form pathological conditions such as cataracts. This oxidative stress ability can be measured by the malondialdehyde (MDA) biomarker. Binahong leaves (Anredera cordifolia (Tenore) Steenis) are native plants from Indonesia that are used to treat various diseases including cataract treatment. Binahong leaf (Anredera cordifolia (Tenore) Steenis) has a high amount of flavonoids and is rich in antioxidants that can be used to treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Quantity of MDA as a factor of lipid peroxidation was measured in the presence of 0.5 % thiobarbiturate and 20 % trichloroacetic acid in a thermoblock (95ᵒC) for 30 min. After cooling and centrifuging (1500× g ) at 25ᵒC for 5 min, absorption was obtained at 535 nm and with tetraethoxypropane as the standard [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…Quantity of MDA as a factor of lipid peroxidation was measured in the presence of 0.5 % thiobarbiturate and 20 % trichloroacetic acid in a thermoblock (95ᵒC) for 30 min. After cooling and centrifuging (1500× g ) at 25ᵒC for 5 min, absorption was obtained at 535 nm and with tetraethoxypropane as the standard [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…According to the ethanol extract of the leaves of the binahong plant, the lens group of the goat lens induced with glucose and the addition of the binahong (Anredera cordifolia (Tenore) Steenis) extract exhibited more transparent results than the lens group induced with 55 mM glucose concentration. Binahong can suppress malondialdehyde generation at doses of 100 or 200 μg/mL [ 101 ]. In another study, it was stated that Lupeol, a pentacyclic triterpenoid isolated from Vernonia cinereal , was effective in the treatment of cataracts in the eye lens of Sprague Dawley rats induced by selenite from the results of testing biochemical parameters such as activity of SOD, CAT, GPx, GR, GST, Ca 2+ ATPase, glutathione, ROS, and lipid peroxidation product (malondialdehyde) were found to be effective in the treatment of cataracts with lupeol [ 100 , 102 ].…”
Section: Methodsmentioning
confidence: 99%
“…In this process, they are causing oxidative stress by reacting with different cellular components such as lipids, proteins, nucleotides and other macromolecules [28,37,38] . During oxidative stress, the levels of the oxidative enzyme will increase, and antioxidant enzymes levels will decrease [39,40] , and the cellular component damage will occur through lipid peroxidation, i.e., increased levels of TBARS levels indicated by MDA [41,42] . The antioxidant activity of A. odorata extracts results showed that good inhibition of free radicals in in vitro study against tested free radicals and in in vivo study results supports the in vitro results with their capability in ameliorating the levels of the antioxidant enzyme, i.e., rise in catalase and SOD levels and decrease the cellular component damages in the body (Tables 3 and 4).…”
Section: Sterolsmentioning
confidence: 99%